Activated microglia release β−galactosidase that promotes inflammatory neurodegeneration - Kitchener, Emily J. A.; Dundee, Jacob M.; Brown, Guy C. (Frontiers in Aging Neuroscience, 2024)
Beta (β)-galactosidase is a lysosomal enzyme that removes terminal galactose residues from glycolipids and glycoproteins. It is upregulated in, and used as a marker for, senescent cells. Microglia are brain macrophages implicated in neurodegeneration, and can upregulate β-galactosidase when senescent. We find that inflammatory activation of microglia induced by lipopolysaccharide results in translocation of β-galactosidase to the cell surface and release into the medium. Similarly, microglia in aged mouse brains appear to have more β-galactosidase on their surface. Addition of β-galactosidase to neuronal-glial cultures causes microglial activation and neuronal loss mediated by microglia. Inhibition of β-galactosidase in neuronal-glial cultures reduces inflammation and neuronal loss induced by lipopolysaccharide. Thus, activated microglia release β-galactosidase that promotes microglial-mediated neurodegeneration which is prevented by inhibition of β-galactosidase.